Literature Review of Optimization Techniques for Chatter Suppression In Machining - A. R., Yusoff; Mohamed Reza Zalani, Mohamed Suffian; Mohd Yusof, Taib (Faculty Mechanical Engineering, UMP, 2011)
Chatter produces a poor surface finish, high tool wear, and can even damage machine tools because of the regenerative effect, the loss of contact effect, and the mode coupling effect. Various research works have investigated the suppression of chatter by either passive or active methods, such as by applying absorbers, damping, varied speeds and other alternatives. In this paper, it can be observed that for chatter suppression, optimization focuses on spindle design, tool path, cutting process, and variable pitch. Various algorithms can be applied in the optimization of machining problems; however, Differential Evolution is the most appropriate for use in chatter suppression, being less time consuming, locally optimal, and more robust than both Genetic Algorithms, despite their wide applications, and Sequential Quadratic Programming, which is a famous conventional algorithm.